Preparation and effectiveness of slow‐release silicon fertilizer by sintering with iron ore tailings. Issue 3 (17th October 2017) - Hu, Pan; Zhang, Yihe; Zhou, Yurui; Ma, Xi; Wang, Xinke; Tong, Wangshu; Luan, Xinglong; Chu, Paul K.
Abstract : Recycling of iron ore tailings (IOT) which are by‐products of iron ore processing has attracted attention but there have been few studies on their use as fertilizers. In this study, slow‐release silicon fertilizers are prepared from iron tailings by solid‐phase sintering and characterized by X‐ray diffraction (XRD) and scanning electron microscopy (SEM). The solubility results acquired from the optimal sample (Si‐IOT) indicate that the available SiO2 is 20.77% and that of available K2 O is 18.43% in 0.50 mol L −1 HCl. For 10 g of Si‐IOT in 200 mL of distilled water at 25°C, the cumulative release of K2 O is 4.32% in the first day and 19.4% in 28 days and that of SiO2 is 2.12% in the first day and 16.30% in 28 days. The performance satisfies the Chinese national standard for slow‐release fertilizers and Chinese agricultural standard for silicon fertilizers. The results obtained from Si‐IOT pertaining to release of heavy metals indicate that heavy metals will not affect the quality of the crops and pakchoi growth is improved. Hence, they are potential raw materials for slow‐release silicon fertilizers. © 2017 American Institute of Chemical Engineers Environ Prog, 37: 1011–1019, 2018